Targeting the Oxytocin System: New Pharmacotherapeutic Approaches. (January 2019) - Gulliver, Damien; Werry, Eryn; Reekie, Tristan A.; Katte, Timothy A.; Jorgensen, William; Kassiou, Michael
Abstract : Deficits in social behavioral domains, such as interpersonal communication, emotion recognition, and empathy, are a characteristic symptom in several neuropsychiatric disorders, including schizophrenia and autism spectrum disorder (ASD). The neuropeptide oxytocin (OT) has emerged as a key regulator of diverse social behaviors in vertebrates and, thus, has been identified as a potential therapeutic target for improving social dysfunction. In recent years, the field of OT research has seen an explosion of scientific inquiry, producing a more comprehensive picture of oxytocinergic signaling and the pathways that regulate its release and degradation in the brain. In this review, we provide an analysis of how this information is being exploited to accelerate the discovery of novel oxytocinergic therapeutics. Highlights: The OT system is involved in the regulation of social behavior, and has been identified as a therapeutic target in neuropsychiatric disorders characterized by deficits in social behavior. The neurobiological basis of oxytocinergic actions is now being elucidated, creating unprecedented opportunities for developing therapeutics that modulate OT signaling. Novel ligands targeting the OT receptor display functional bias and exploit receptor dimerization, opening a range of potential investigative and therapeutic avenues. Emerging strategies that potentiate endogenous OT signaling could also provide a new and advantageous approach to modulate social behavior.